Hydrodynamic Analysis of High-Speed Vessels in Shallow and Deep Water Using CFD - Budi Utomo; S Samuel; Parlindungan Manik; Chiquita Azaria; Syaiful Tambah Putra Ahmad; Zhang Yongxing (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2023)
Differences in the depth of the water surface affect the hydrodynamics of the ship so there is a possibility that the ship will behave differently in deep water and shallow water. The surface flow generated by the hull varies radically due to the speed of the ship and the effects of water depth. At a certain speed, the ship experiences a critical speed condition, which will affect the total resistance of the ship. This study examines the Fridsma ship's resistance to differences in water depth at several speeds. Numerical computation is used in this study to simulate the characteristics of a planing hull form. The Finite Volume Method (FMV) is used to observe fluid flow due to differences in water level with the RANS (Reynolds-Averaged Navier - Stokes) equation in predicting ship resistance. K-ε was modeled as a turbulent and volume of fluid (VOF) model to represent the air and water phases. This study uses a morphing grid mesh to analyze the shape of the hull in numerical simulations. The total resistance of Fridsma in shallow waters increased at each speed when compared to the total resistance in deep waters. On average in deep waters, it can reduce the total resistance by around 22.34% compared to shallow waters. This is caused by the squat phenomenon that occurs in the hull.